2008
DOI: 10.1136/jme.2006.018507
|View full text |Cite
|
Sign up to set email alerts
|

The role of nurses in euthanasia and physician-assisted suicide in The Netherlands

Abstract: The results show substantial differences between the intramural sector (hospitals and nursing homes) and the extramural sector (home care), which are probably linked to the organisational structure of the institutions. Consultation between physicians and nurses during the decision-making process needs improvement, particularly in home care. Some nurses had administered euthanatics, although this task is by law exclusively reserved to physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 11 publications
0
45
0
2
Order By: Relevance
“…Similar findings have been reported in other countries. 14,15 In our study, administration of the life-ending drugs by the nurse occurred more frequently in the cases without an explicit request from the patient than in the cases of euthanasia. Previous studies have shown that nurses believe an explicit request from the patient is required when accepting an assisting role in dying.…”
Section: Researchmentioning
confidence: 87%
See 4 more Smart Citations
“…Similar findings have been reported in other countries. 14,15 In our study, administration of the life-ending drugs by the nurse occurred more frequently in the cases without an explicit request from the patient than in the cases of euthanasia. Previous studies have shown that nurses believe an explicit request from the patient is required when accepting an assisting role in dying.…”
Section: Researchmentioning
confidence: 87%
“…It is also unknown whether our findings are generalizable to practices elsewhere in the world, although the studied practices and legal prohibition of nurses' involvement in administering life-ending drugs exists worldwide. [1][2][3][4][5]10,11,14,15,22,33,34 Conclusion By administering life-ending drugs at the physician's request in some cases of euthanasia, and even more so in cases without an explicit request from the patient, the nurses in our study operated beyond the legal margins of their profession. Future research should closely monitor and examine the involvement of nurses in these practices nationally and internationally to allow comparisons between countries with and without euthanasia legislation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations